Estudo comparativo entre quantitativos previstos e realizados em uma obra de construção civil em Curitiba - Paraná - Miotto, Bruna Fiore (2014)
This paper analyses the budgeting difference – quantities and costs – estimates and actual bid results, of a constructed facility in the city of Curitiba - PR. Every construction work is detailed and analyzed separately, aiming to identify the services responsible for the inaccuracy of construction cost estimates. It discusses the concepts of project planning and the available resources, the types of construction cost estimates and project schedule. The main purpose of this paper is to compare the data out of a study case. This research is accompanied by a probabilistic study, through error propagation, helping to determine the certainty of the cost variation. It recommends that the constructor should be attentive to the pre-design phase of the project, costs estimation and an accurate list of quantities. It infers that there is a direct influence on the pre-phase planning and the final cost variation.